Patient-reported outcome measures for anticipatory grief: a systematic review - Wang, Shiyuan; Gu, Wangyang; Zhang, Ling; Liu, Wei; Tao, Zeqin; Cheng, Yanrong; Liu, Wenlin; Zhao, Xiaoting; Tu, Wen; Gao, Xing (Frontiers in Psychology, 2026)
BackgroundAnticipatory grief (AG) refers to the experience of grief symptoms by patients or their caregivers in response to life-threatening illnesses, even before an actual loss has occurred. The selection of valid and reliable patient-reported outcome measures (PROMs) to assess AG is essential for early identification, effective intervention, and the reduction of prolonged grief disorder. This study summarizes psychometric properties of AG PROMs and recommends the most effective PROMs.MethodsNine databases (PubMed, EMBASE, Web of Science, CINAHL, Cochrane Library, PsycINFO, CNKI, Wanfang, China Biology Medicine Database) were searched from inception to December 2024. Search terms include “preparatory” or “preparedness” or “pre-loss” or “pre-death” or “anticipatory,” “grief” or “mourn” or “bereave,” “surveys and questionnaires” or “assess” or “instrument” or “measure” or “inventory” or “scale” or “interview.” Eligible studies included those reporting the development or validation of any AG assessment for patients with chronic illnesses and their informal caregivers. Extracted psychometric properties encompassed content validity, structural validity, internal consistency, cross-cultural validity, reliability, measurement error, criterion validity, hypothesis testing, and responsiveness. We conducted a reliability generalization meta-analysis of internal consistency (Cronbach’s alpha) for identical AG PROMs across different studies. Quality assessment, measurement property ratings, synthesis, and modified grading of evidence were conducted following the COSMIN methodology for systematic reviews.ResultsA total of 20 studies comprising of 13 AG PROMs were included. 2 PROMs were designed for patient assessment, and 11 targeted informal caregivers. PG-12 demonstrated high-quality evidence in assessing informal caregiver AG, with satisfactory content validity and internal consistency, supporting grade A. MM-CGI-CCPS showed insufficient evidence for structural validity and internal consistency, warranting grade C; the remaining tools are suggested as grade B due to limited evidentiary support.ConclusionThis review confirms PG-12 as a grade A PROM for measuring AG in informal caregivers. However, no grade A PROMs were identified for assessing AG in patients. Future studies are needed to further validate the methodological quality and measurement properties of PROMs used in patient populations. Significant concerns remain regarding other existing PROMs, particularly in content validity, structural validity, cross-cultural adaptation, measurement error, and reliability, which increase uncertainty in available evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024624205, identifier (CRD42024624205).